1994
DOI: 10.1037/0882-7974.9.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the sensitivity of two self-report depression scales in older depressed inpatients.

Abstract: Both the Geriatric Depression Scale (J. A. Yesavage et al., 1983) and the Beck Depression Inventory (A. T. Beck, A. J. Rush, B. F. Shaw, & G. Emery, 1979) were less effective in identifying depressed men than women in a sample of 191 geriatric psychiatric inpatients with major unipolar depression. From one quarter to one half of the men were missed cases, depending on the cutoff score used. Separate cutoff scores for older men and women on depression screening instruments may be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The alphas of 0.89 and 0.88 for the overall sample for BDI-II and GDS total scores, respectively, are satisfactory and consistent with previous research with older adults (Parmelee et al, 1989;Steer et al, 2000;Norris et al, 2004). Significantly higher mean scores on the BDI-II and GDS were found for women than men, which is consistent with previous research that found a gender difference in the means of the overall scores for the BDI-II with medical patients (Arnau et al, 2001) and for the GDS with older adults (Parmelee et al, 1989;Allen-Burge et al, 1994). In addition, for both the BDI-II and GDS, mean scores were significantly different between non-depressed and depressed participants for the SCID-I/NP diagnostic categories, providing criterion-related evidence to support the use of total scores to screen for depression in cardiac patients.…”
Section: Discussionsupporting
confidence: 91%
“…The alphas of 0.89 and 0.88 for the overall sample for BDI-II and GDS total scores, respectively, are satisfactory and consistent with previous research with older adults (Parmelee et al, 1989;Steer et al, 2000;Norris et al, 2004). Significantly higher mean scores on the BDI-II and GDS were found for women than men, which is consistent with previous research that found a gender difference in the means of the overall scores for the BDI-II with medical patients (Arnau et al, 2001) and for the GDS with older adults (Parmelee et al, 1989;Allen-Burge et al, 1994). In addition, for both the BDI-II and GDS, mean scores were significantly different between non-depressed and depressed participants for the SCID-I/NP diagnostic categories, providing criterion-related evidence to support the use of total scores to screen for depression in cardiac patients.…”
Section: Discussionsupporting
confidence: 91%
“…. However, the elderly, especially males, report depressed mood more infrequently than the adult and the young (Allen-Burge et al, 1994) and were less likely to have been known to psychiatric services (Salib and Green, 2003). In the province of Verbania a high prevalence of older people that correlate the suicide to mental disease has been found.…”
Section: Discussionmentioning
confidence: 98%
“…7 However, few at-risk older adults, particularly men, 14 spontaneously report symptoms of distress and/or thoughts of suicide, 15 which can impede the accurate detection of suicide risk. Primary care physicians often have difficulty asking their patients about sensitive topics such as suicide 1620 ; however, they are more likely to do so with patients who present with symptoms of major depressive disorder or those who request an anti-depressant.…”
mentioning
confidence: 99%
“…1,3234 Furthermore, research supports more subtle approaches that can be used to assess the presence of suicide ideation among older adults 33 given their general tendency to downplay the presence and severity of depressive symptoms. 14,15 Hence, in the present study we assessed whether the GDS 29 has acceptable operating characteristics in identifying older primary care patients who express a desire for death or for suicide. We also examined potential sex differences in the scale’s accuracy given sex differences in older adults’ suicide ideation, 4,34 rates of suicide, 2,35 and symptom reporting.…”
mentioning
confidence: 99%
See 1 more Smart Citation